Binuclear aluminum complexes with amine–imine type ligands derived from 1, 3-benzenedialdehyde: synthesis, structures and their catalytic properties in ring-opening polymerization. Issue 6 (18th March 2016) - Wu, Chuanguang; Zhou, Hui; He, Mina; Su, Qing; Li, Guanghua; Wu, Qiaolin; Mu, Ying
Abstract: Reaction of 1, 3-bis(imino)benzenes with a stoichiometric amount of LiAlH4 in THF yields iminoaminobenzenesL1 andL2 . Further reaction of iminoaminobenzenesL1 andL2 with an equivalent of AlR3 in toluene affords macrocyclic binuclear aluminum complexes1a, 1b, and2a . These macrocyclic aluminum complexes were characterized by 1 H NMR, 13 C NMR, and IR spectroscopy. The molecular structures of1a, 1b, and2a were further confirmed by X-ray crystallography. X-ray diffraction analysis revealed that1a, 1b, and2a adopted a distorted tetrahedral geometry around aluminum. These complexes have efficient activities toward ring-opening polymerization of ε -caprolactone in the presence of benzyl alcohol. Abstract :